Der österreichische Werbefilm Die Genese eines Genres von seinen Anfängen bis 1938 - Moser, Karin (Werbung - Konsum - Geschichte, 2019)
Filmed commercials are part of the culture of remembrance and of corporate and film history. When did this form of advertising begin? Who were the first sponsors and were advertising films made differently at that time than now? The monograph addresses these questions using the example of Austria. Starting from the early period of cinematography, it researches the development and establishment of the genre of the commercial in Austria until 1938.